EVALUATION OF PAVEMENT THICKNESS FOR THE APRON DEVELOPMENT AT SULTAN HASANUDDIN AIRPORT MAKASSAR USING THE ACN/PCN METHOD - Dewi Rintawati; Sari, Christina; Andhita Vinka Octaviani (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2025)
Sultan Hasanuddin Airport in Makassar has experienced an 11% increase in passenger traffic and a 9% annual growth in aircraft movements. In 2019, Sultan Hasanuddin Airport undertook an apron development to address these needs. An evaluation of the development was conducted to determine the appropriate apron pavement thickness. Aims: The aim of this study is to evaluate the apron pavement thickness by comparing conventional calculations with the existing conditions. Methodology and results: The calculation methods compared three approaches: conventional methods and the ACN/PCN system. The study results using the ACN/PCN method require aggregate design thicknesses for the pavement. The thicknesses for each apron development area are 84 cm, 91 cm, and 93 cm. Conclusion, significance and impact study: Comparing the results of the three methods with the current conditions, which are 95 cm and 110 cm, the pavement thicknesses from the 2019 development—84 cm, 91 cm, and 93 cm—are safe for up to 20 years and are capable of supporting the planned B777-300 aircraft according to the design specifications.